A cross-sectional observational study of geriatric dermatoses in a Tertiary Care Hospital of Northern India - Reetu Agarwal; Loknandani Sharma; Ajay Chopra; Debdeep Mitra; Neerja Saraswat (Wolters Kluwer Medknow Publications, 2019)
Introduction: Geriatric dermatoses are one of the most common reasons for day-to-day consultation in the elderly. Over the past few years, understanding of the pathophysiology of skin changes in the geriatric age group has improved and has paved the way for better therapeutic options. There are only a few studies conducted in India about the geriatric dermatoses. This article reviews the various physiological and pathological changes of aging, dwelling on the role of intrinsic and extrinsic factors in the pathogenesis of aging skin thus better understanding of this emerging branch in dermatology leading to enhance resource management for elderly population. Materials and Methods: This is a cross-sectional observational study carried out on 500 consecutive patients aged 60 years and above in Department of Dermatology of a Tertiary care hospital of Northern India after meeting the inclusion and exclusion criteria. Results: Out of 500 patients studied with male to female ratio of 1.4, wrinkles followed by cherry angiomas were the most common physiological cutaneous manifestations, and infective dermatoses followed by allergic contact dermatitis were the most common pathological conditions seen. Few rare cases were also seen during the study such as cutis marmorata, delusion of parasitosis, and sweet syndrome in case of acute myeloid leukemia. Conclusion: Geriatric dermatology is an emerging branch in dermatology, and an update on this, will go a long way to effectively manage these patients. A thorough knowledge of the epidemiology as well as gender distribution of dermatological diseases in geriatric population in the tertiary care hospital will help in assessing health status and health care needs related to skin for better allocation of resources, distribution of material and manpower, and help health care providers in better decision-making resulting in higher clientele satisfaction.